Lugares de memória das culturas negras em Bragança-Pará: experiências com o ensino de História - SILVA, Tomé Montanaro Ferreira da (Universidade Federal do Pará, 2020)
The present work aims to examine the places of memory of black cultures in Bragança, in the State of Pará, based on experiences in teaching history with elementary school students. To this end, we have placed memorial places that served as points to be visited and investigated by elementary students. The questions developed were based on what students know about blacks, from the stories told in the classroom, which date back to the days of slavery and record the black African presence in the region, and the cultural imprints of that presence still alive today. After the previous readings that guided the elaboration of the project that was designed as an action research, the methodology of work with the students was divided in two great moments: application of questionnaires and visits to the selected sites. As for the application of questionnaires, these were made as a survey of the students about the specific theme of the life of the Negro in history and of how in contemporary times there are still traces that are delimited as part of the daily life of Bragança. In the second point, that of the methodology, six places for visitation were chosen. In this second case, formal teaching in the classroom and teaching in other spaces were articulated in order to enable students to learn history in places that are part of their everyday life, but which are silenced. Some of what is defined as black culture is part of the context of the history of Bragança, although some are part of the students' experience, they do not associate as a structuring part of a process that comes from a period that was characterized in the country as black African slavery, and is energized to the present. Strategies were designed that made the students relate and perceive that in the spaces where they live pulsate the stories and memories in such a way that the places are also object of studies whose student's look can be guided by the teacher.